(untitled) (Economics and region, 2022)
The article is devoted to topical issues of the evolution of theoretical views on international business activities under franchising conditions. The factors that influenced the development of the international franchise were studied. The external factors of choosing the target market for the franchise network are outlined, in particular, political, economic, demographic, and cultural. Factors affecting the franchisor’s decision to enter the foreign market, which are components of the exit risk assessment model, were identified. A model for assessing the risk of franchise network internationalization has been developed. It was found that franchising is not only a form of doing business, but also the basis of the expansion strategy of many companies. The concept of expansion, as a rule, is associated with growth and development. Thus, this applies to both quantitative aspects (increasing the number of resources and / or units) and quality (increasing the value of resources and / or brands). It is noted that, however, the behavior of enterprises focused on these changes is not always called expansion. They can be the result of two different ways of behaving – adapting to changes in the environment (passive attitude) or anticipating these changes (active attitude). The first type of behavior is related to survival, while only in the second case we can talk about expansion. It was revealed that the franchising phenomenon acquires special importance in the transnational space. Since franchising is a form of international expansion, which allows to strengthen the competitive potential mentioned above. There are many forms of internationalization under which a franchise is classified. In particular, a franchise can be characterized as a form of resource expansion, since in this case certain resources (the subject of the franchise) are transferred. It is also a form of implementation of many strategic orientations of enterprises, especially regiocentric, global and transnational. This is possible because this formula makes it possible to combine the strategy of differentiation with the standardization of the activities carried out, achieved through the repetition of activities.